Keputusan Investasi dari Perspektif Perilaku Keuangan - Budiman, Johny (Journal of Global Business and Management Review, 2019)
This study aims to analyze behavioural factors that could affect the investment decision such as overconfidence, disclosure, past performance, advice, and investor?s competence. Whereas the sample in this paper are stock investors in  Batam City. The number of questionnaires distributed were 120 sheets and all questionnaires were successfully answered. The collected data will be analyzed with multiple linear regression.The results of this study indicate that overconfidence, disclosure, and investor's competence have a significant positive effect, advice  has a significant negative effect, and past performance has no significant effect.